Digital transformation and corporate strategy - A. L. Denisova; A. N. Lopatnikov (Управление)
The term digital transformation has been widely discussed and extensively promoted both to and by companies in every industry to become overused. While generally accepted as a boon and often marketed as the only alternative to extinction for a firm, digital transformation remains a significant challenge for those assigned to implement it. We offer an alternative narrative digital transformation, which we argue is better described as going «more digital». The extent to which going more digital becomes transformative depends on the industry and the ability of a firm to change the business model and organizational skills, and corporate culture. We extend the discussion on why digital transformation is in most cases unrelated to business strategy and provide examples of when and how it may become part of a corporate strategy toolbox. A simplified model of a business as a network of processes and decisions helps illustrate why digital technologies first spread in the process domain but can become strategic and transformative when adopted to the decision domain. The latter also brings yet unquantifiable risks and uncertainties. We suggest future research to focus on the value created by going «most digital» in both process and decision domains and risks to companies and the economy.